2006
DOI: 10.1111/j.1439-0450.2006.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological, Bacteriological and Molecularbiological Survey of Paratuberculosis (Johne's Disease) in Austrian Cattle

Abstract: Paratuberculosis (Johne's disease) is a chronic infectious disease of ruminants, caused by Mycobacterium avium subspecies paratuberculosis (MAP). Because of its long incubation period, high economic losses, difficulties in diagnosis and possible links to Morbus Crohn in humans, paratuberculosis is one of the most important diseases of ruminants today. An abattoir-based nationwide survey on the occurrence of MAP in the Austrian cattle population was performed using serology (SVANOVIR-ELISA) as well as culture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
11
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
4
11
1
5
Order By: Relevance
“…The low agreement between tests results has been also reported before (Muskens et al, 2003;Glanemann et al, 2004;Dreier et al, 2006) and could be explained due to the fact that ELISA negative or ELISA false-positive results have a low probability of delivering a positive culture result if just a single sampling is planned as normally done in a crosssectional study, which was the case of the present study (Sweeney et al, 2006). Similar results on low agreement between ELISA and culture (Fernández-Silva et al, 2011b) and ELISA and PCR to MAP (Fernández-Silva et al, 2011a) were found in previous studies in asymptomatic animals from herds of the same dairy region.…”
Section: Discussionmentioning
confidence: 64%
“…The low agreement between tests results has been also reported before (Muskens et al, 2003;Glanemann et al, 2004;Dreier et al, 2006) and could be explained due to the fact that ELISA negative or ELISA false-positive results have a low probability of delivering a positive culture result if just a single sampling is planned as normally done in a crosssectional study, which was the case of the present study (Sweeney et al, 2006). Similar results on low agreement between ELISA and culture (Fernández-Silva et al, 2011b) and ELISA and PCR to MAP (Fernández-Silva et al, 2011a) were found in previous studies in asymptomatic animals from herds of the same dairy region.…”
Section: Discussionmentioning
confidence: 64%
“…요네병은 Mycobacterium avium subspecies paratuberculosis (MAP)에 의해 발생하며 주로 소, 면양, 산양 등의 반추동물에 서 만성쇠약을 일으켜 전세계적으로 양축산업에 커다란 경제 적 손실을 일으키는 질병이다 [3,5,11,12,14,17,20]. 또한 MAP가 사람에서 만성 염증성 장질환으로 알려진 크론병과 관련이 있을 것이라는 증거들이 보고되면서 공중보건학상 중요한 질 병으로 여겨지고 있다 [5,6,11,12,[14][15][16].…”
unclassified
“…또한 MAP가 사람에서 만성 염증성 장질환으로 알려진 크론병과 관련이 있을 것이라는 증거들이 보고되면서 공중보건학상 중요한 질 병으로 여겨지고 있다 [5,6,11,12,[14][15][16].…”
unclassified
See 2 more Smart Citations